(3GNJjGQ GdCMcGe Ydi GdChLg GdKdGKI ef GdHQhL GdEKfi YTQs - (3GdMcje hGdjS GdeUQjs ((3GdfLa s)
(3ChdgG (B:s
(3Cf JYQa UaGJ GdhLhg GdKdGKI ef cd HQL ef GdHQhL GdGKfi YTQ HdhfgG hUhQgG HQL GdMed (B: (3GdhLg GdChd efg , jchf CUgH GdTYQ s
(3BNQgG (B:s
(3Ch CSdegG Edi GdehJ , hcPdc GdeQCI agPg GdhLhg GGdKdGKI ef GdHQhL GdEKfi YTQ jMJGL EdjgG ai GdeSGFd hZjQgG aJPcQgG ai GdLhGH Ydi eG PcQJ dc ai GdhUa s
(3Vef eLehY s
(3fbdgG GdfGSN ef fSNI cJHgG eDef GdcTejQi LOjO GdESdGes
(3ai HdOI CUagGf SfI (B1086(3g` hHfSNJfG gPg fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B34s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdadcs